Death in the Andes - Vargas Llosa, Mario, 1936-; Grossman, Edith, 1936- (New York : Farrar, Straus and Giroux, 1996)
"In this novel, simultaneous plot lines ranging from an investigation by Corporal Lituma of a mysterious disappearance, to his deputy's love affair with a prostitute, to an Andean community terrorized by Shining Path guerrillas, and the alternating first- and third-person narrators all obscure coherence. Grossman's lazy translation needlessly retains large doses of original Spanish lexicon. An introduction, maps, and a translator's note are badly needed to orient readers not familiar with Peru"--Handbook of Latin American Studies, v. 58.
Keywords: Peru -- Fiction; Political fiction; Detective and mystery stories